Developments in New York 1956 - Kreidler, W. L. (AAPG Bulletin, 1957)
Eighteen wells were completed in the Oriskany gas area, with 4 of the wells completed as producers. Twelve were completed to the Oriskany in the new Allegany State Park field. Medina sandstone drilling totaled 23 wells, with 34.48% for gas storage. There were 458 development oil wells drilled during 1956, and the daily average for pipeline runs amounted to 7,340.5 bbls. Storage of gas in the Oriskany and Medina fields have a total active capacity of around 115 billion CF annually.
Keywords: geology